Synthesis of V-shaped MnO2 nanostructure and its composites with reduced graphene oxide for supercapacitor application. Issue 20 (29th April 2021) - Jangu, Surendra; Satpathy, Biraj Kanta; Raju, Mula; Jacob, Chacko; Pradhan, Debabrata
Abstract : Synthesis of MnO2 nanostructures using a microwave-assisted solvothermal method by varying the acetic acid amount at 150 °C for 15 min. Abstract : A unique V-shaped MnO2 nanostructure is synthesized with a weak acid (acetic acid) using the microwave-assisted hydrothermal technique. To improve the performance of MnO2 in supercapacitor applications, its composite was prepared with reduced graphene oxide (rGO), i.e., MnO2 /rGO, with different weight ratios of MnO2 and rGO. The specific capacitance values of the as-synthesized V-shaped MnO2 nanostructure and MnO2 /rGO nanocomposite were calculated to be 64.75 and 88.95 F g −1 at a current density of 0.5 A g −1, respectively, in 1 M Na2 SO4 electrolyte. Furthermore, a two-electrode asymmetric supercapacitor device was fabricated using the MnO2 /rGO nanocomposite as a positive electrode and activated carbon as a negative electrode. The device has shown energy densities of 25.14 and 17.95 W h kg −1 at 0.25 and 1 kW kg −1 power densities, respectively. These values suggest that the MnO2 /rGO nanocomposite is a promising material for supercapacitor devices.